Upaya Pencegahan dan Penanggulangan Infeksi Kecacingan Anak Sekolah Dasar di Kampung Tablasupa Distrik Depapre Kabupaten Jayapura - Hartati, Risda; J.Imbiri, Meidy; Kawaitou, Leberina (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2021)
Worm infections in Jayapura City were reported through the results of Martila's research, in 2015 showing a high prevalence of worms in school-age children. The study results found that 50% of children were infected with worms in SD Abe Pantai Jayapura City, with the most infections caused by Ascaris lumbricoides (48.5%) and Trichuris trichiura (28.6%). The survey of helminth infections in Jayapura Regency by BTKL in 2018, according to the Papua Provincial Health Office Report 2019, was 24.30%. Community service activities to implement prevention and control of worm infections through worm infection checks, counseling, and proper handwashing practices for 50 elementary school-aged children in Tablasupa Village, Depapre District, Jayapura Regency. The implementation of the activity starts in June-October 2021. The activity results include that school children can practice how to wash their hands properly, the child's fingernails have started to clean and are not extended. The results of the evaluation of the identification of the presence of worm eggs microscopically in 50 samples (100%) were negative. It is recommended for continuous supervision of parents and teachers regarding children's personal hygiene every day. Infeksi Kecacingan di Kota Jayapura dilaporkan melalui hasil penelitian Martila, tahun 2015 menunjukkan tingginya prevalensi kecacingan pada anak usia sekolah. Hasil penelitian ditemukan 50% anak terinfeksi kecacingan di SD Abe Pantai Kota Jayapura, dengan infeksi terbanyak disebabkan oleh Ascaris lumbricoides (48,5%), dan Trichuris trichiura (28,6%). Survei infeksi kecacingan di Kabupaten Jayapura oleh BTKL tahun 2018 menurut Laporan Dinkes Propinsi Papua Tahun 2019 sebesar 24,30%. Kegiatan pengabdian masyarakat dengan tujuan untuk mengimplementasikan upaya pencegahan dan penanggulangan infeksi kecacingan melalui pemeriksaan infeksi kecacingan, penyuluhan dan praktek mencuci tangan dengan benar pada 50 anak usia sekolah dasar Kampung Tablasupa Distrik Depapre Kabupaten Jayapura. Pelaksanaan kegiatan dimulai Bulan Juni-Oktober Tahun 2021 Hasil kegiatan meliputi anak sekolah mampu mempraktekkan cara memcuci tangan dengan benar, kuku tangan anak sudah mulai bersih dan tidak panjang. Hasil evaluasi identifikasi keberadaan telur cacing secara mikroskopis pada 50 sampel (100%) negatif. Disarankan untuk pengawasan terus menerus kepada orang tua maupun guru terkait personal hygiene anak setiap harinya.